Bunch Development of Oil Palm (Elaeis guineensis Jacq.) in Two Sites with Different Rainfall Distribution and Genotypes - , Fahri Arief Siregar ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Palm tree production strongly depends on environmental factors such as climate condition, fertilizer, water availability and the implementation of agronomic techniques and internal factors such genotype potential. The process of oil synthesis requires a highenergyprocess compared toproduction of the vegetative organ, so each factor may restrict this process and in particular the environmental condition would potentially reducethe oil yield production.There are two main sources of carbohydrates for palm growth: carbohydrates that are moved from the stem as the reserve organ or directly from leaves where the photosynthesis processoccurs. The combination between those carbohydrate sources also might be occurring in certain periodswhen there is a lag of photo-assimilate suppliedto the developed bunch. A comparison between the conventional and simplified fruit sampling method was conducted for a more simple and proper procedure to get palm fruit samples. A more detailed experiment which applied in Nested design with 3 replications was constructed for this study which consisted of 3 factors such as the site, genotype, and series of experiment. Two different rainfall distributions between Riau and South of Kalimantan were chosenfor representingthe two different sites. Two contrastinggenotypesbetween high and low productions were selected on each site. Six series of consecutive experimentswith a six-month duration and two-month intervalsbetween each series was implemented toaccommodateforthe variation of rainfall distribution within a year. The genotype factor, the series factor, the combination factor between the genotype and the series were madewithin the site. Some variables in termsof oil yield were observed,such as oil concentration, dry-biomass and oil content in mesocarp. Dynamic carbohydrates from all aspects such as carbon assimilation, carbon reserve, and carbon utilization for bunch development were analyzed torepresent the correlation between sourcesand sink relationships. Climate variables were recorded and computed on a daily basis using automatic weather stationsthat were installed at eachsite of the experiment. A simplified sampling method was properly used to observe the oil concentration of the mesocarp which begins from the top part of bunch and then goes downward to the basal site. The period of severe dry season of more than 3 consecutive months such as in South of Kalimantan resulted in a more negative impact to the oil yield production. The genotype with high production performance ateach site wassignificantly higher than the low genotype productivity related tothe production of oil yield per bunch. The mobilization of NSC total on thephythomer scale was evidencedin the stem and petiole organ and was greater compared to the leaves and mesocarp. Starch was the most mobilizing sugar in stem, while glucose is in petiole during the oil synthesis. Sugar mobilization depends on the balance between its reserve and demand during the oil synthesis, as it may be mobilized from the stem as a reserve organ or directly from the leaves or even a combination from both mechanisms.Declining photosynthesis activity at maturation stages of a developed bunchis related to the declining oil accumulation and carbohydrate demand for oil synthesis activity at the same period.